Effect of ultrasound-guided right stellate ganglion block on perioperative atrial fibrillation in patients undergoing lung lobectomy: a randomized controlled trial - Ouyang,Ru (2020)
Abstract Objective: To observe the effects of preoperative right stellate ganglion block on perioperative atrial fibrillation in patients undergoing lung lobectomy. Methods: Two hundred patients who underwent a scheduled lobectomy were randomly divided into the S and C groups. The S group was injected with 4 mL of 0.2% ropivacaine under ultrasound guidance, and the C group did not receive stellate ganglion block. The patients underwent continuous ECG monitoring, and the incidences of atrial fibrillation and other types of arrhythmias were recorded from the start of surgery to 24 hours after surgery. Results: The respective incidences of atrial fibrillation in the S group and the C group were 3% and 10% (p = 0.045); other atrial arrhythmias were 20% and 38% (p = 0.005); and ventricular arrhythmia were 28% and 39% (p = 0.09). Conclusions: The results of the study indicated that preoperative right stellate ganglion block can effectively reduce the incidence of intraoperative and postoperative atrial fibrillation.